2004
DOI: 10.1291/hypres.27.243
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between the Awareness of Salt Restriction and the Actual Salt Intake in Hypertensive Patients

Abstract: A 24-h home urine collection was conducted to estimate accurate salt intake in hypertensive outpatients.Using 24-h urinary creatinine excretion as a criterion for success, urine samples were obtained from 534 hypertensive patients. The urinary salt excretion of hypertensive outpatients ranged widely from 1.5 to 23.4 g/day (mean value 9.7 3.9 g/day). Urinary salt excretion was higher in males than in females (10.6 4.0 vs. 9.2 3.7 g/day, p 0.01). Based on the questionnaires, the patients were divided into salt-c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
38
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 63 publications
(43 citation statements)
references
References 20 publications
3
38
1
Order By: Relevance
“…However, there was no significant association between urinary salt excretion and awareness of salt restriction at baseline (data not shown). This observation is compatible with previous findings by Ohta et al that there is no relationship between awareness of salt restriction and the actual salt intake evaluated by 24-h urine collection (18). Since subjective awareness of salt restriction may not necessarily be reflected in actual salt reduction, monitoring of salt excretion seems extremely important to educate the population about the health benefits of salt restriction.…”
Section: Discussionsupporting
confidence: 90%
“…However, there was no significant association between urinary salt excretion and awareness of salt restriction at baseline (data not shown). This observation is compatible with previous findings by Ohta et al that there is no relationship between awareness of salt restriction and the actual salt intake evaluated by 24-h urine collection (18). Since subjective awareness of salt restriction may not necessarily be reflected in actual salt reduction, monitoring of salt excretion seems extremely important to educate the population about the health benefits of salt restriction.…”
Section: Discussionsupporting
confidence: 90%
“…On the other hand, salt intake has been reported to be high in the Japanese population (12). We have previously reported that an awareness of the importance of salt restriction is not associated with actual salt restriction in hypertensive outpatients (13). Since the average urinary salt excretion was 9.7±3.9 g/day in that study, achieving the level of salt restriction suggested by the guidelines would seem to be difficult in the Japanese population.…”
Section: Introductionmentioning
confidence: 58%
“…In the present study, however, urinary salt excretion at the last visit was significantly lower than that at the first visit. We have previously reported that there is no obvious reduction in the actual salt intake in saltconscious patients (13). Thus, repeated monitoring of urinary salt excretion, along with providing feedback to patients and follow-up counseling, seem to be the most important and practical way to achieve a reduction of salt intake in individual hypertensives (13,19).…”
Section: Discussionmentioning
confidence: 99%
“…10 In our previous survey on hypertensive outpatients, this reduction in salt intake was not achieved even in patients who are conscious about salt restriction. 11 Long-term compliance with salt restriction in hypertensive patients was also extremely low. 12 As it is difficult to change dietary habits in adults, education or intervention to reduce salt intake during childhood is very important.…”
Section: Introductionmentioning
confidence: 99%